The cultural politics of discourse on school leadership: a case of China. Issue 1 (2nd January 2022) - Wei, Wei
ABSTRACT: There has been a global convergence of policies attempting to standardize the practices and competencies of school leaders. This policy convergence highlights a similar set of leadership practices that are expected for effective school leaders, and contributes to the constitution of a global dominant discourse on school leadership. This study is a critical policy analysis of a standards-based leadership policy introduced in China, and identified three themes emphasizing Chinese traditional culture, morality, as well as the authority of the Chinese Communist Party and the central government. These three themes are configured by the cultural politics that are situated in the context of China. This article concludes that the global dominant discourse is contextualized and shaped by the power relations and politics that resonate with China's cultural traditions, developmental strategies, and school leadership system.